A influência da cor da pele no tempo de atendimento de pacientes negros em um contexto clínico - Silva, Renata Pimentel da (2018)
The aim of this thesis was to test the hypothesis that physicians spend more time consulting white patients than black patients, and that time bias is related to a patient's quality of diagnosis. Three empirical studies were carried out to test the hypothesis that physicians spend more time on white patients than on black patients. Study 1, with an observational and transversal character, was carried out in a Reference Center for Health Care (CRAS). The study consisted of the observation of medical appointments in which the duration of the consultations was timed. A total of 169 observations were made, of which 78 were white patients, 57 were black and 34 were brown. A one-way ANOVA showed that physicians invested less time in the care of black patients (M = 5.31) than in white (M = 7.23) and brown patients (M = 7.36) (F = 4.09 , p = 0.02) .This result occurred in all the medical specialties observed, demonstrating that the variation in the time of care occurs, in fact, by the patients' skin color. Although this study proves the ITB effect in the context of health, it was considered necessary to analyze this phenomenon in a more controlled way. Therefore, we conducted study 2 with the objective of evaluating the time investment differentiation in the evaluation of black and white patients and the possible consequences of this differentiation, so that we evaluated the bias in the medical conducts expressed in the number of diagnostic hypotheses that they raise for a low complexity clinical case. This is an experimental interparticipant study. A total of 67 medical students from a public university, with a mean age of 25.36 years (SD = 2.99), were mostly male (53.7%). Participants answered the experiment in the E-prime software and performed a Clinical Case Evaluation, where participants were presented with a patient care chart, with instructions to carry out an evaluation of the case and the indication of diagnostic hypotheses. SPSS 20 software was used for the analysis of the time invested in the analysis of the clinical case. An ANOVA was performed, whose results indicated that there was no main effect of the skin color at the evaluation time, F (2, 76) = 1.0, ns. However, when comparing the number of diagnostic hypotheses and the patient's skin color, it was found that white patients received a greater number of diagnostic hypotheses (M = 1.84, SD = 0.83) than black patients (M = 1.24, SD = 0.72) and the patient without color identification (M = 1.35, SD = 0.77) and this difference was significant (F (2.64) = 3.56, p <0.05). Study 3 aimed to demonstrate that the bias in the treatment given to patients based on the color of their skin is a consequence of ITB. Sixty students from the medical school, with a mean age of 25.20 years (SD = 3.45) participated in the study, most of them men (51.7%). A methodological plan similar to the previous study was followed, but a delineation among participants was adopted, so that each participant evaluated three clinical cases. Through a multilevel regression analysis, it can be shown that the white patient (M = 0.54, SD = 0.08) was invested more time than the black patient (M = 0.36, SD = 0.08 ). The results also showed that the time of diagnosis is mediating the number of diagnostic hypotheses, so that the more time invested, the greater the number of diagnostic hypotheses (90% CI: 0.01; 0.19). Together these results contribute to the study of implicit discrimination motivated by prejudice.